'Feminist' in the sociology of sport: An analysis using legitimation code theory and corpus linguistics. (2020) - Brooke, Mark
Abstract: The research explores the functional distribution of the term 'feminist' in the Sociology of Sport. To do this, new conceptual tools from Legitimation Code Theory's (LCT) dimension of Semantics are enacted. A 650, 000-word corpus from 100 published articles in peer reviewed, internationally ranked journals was compiled. Constructions with 'feminist' as both a noun and attributive adjective were identified. There were 2044 occurrences of 'feminist' with a distribution of 229 different constructions. 'Feminist' is a complex term, especially in its form as attributive adjective, and therefore, in LCT terms, represents relatively strong epistemic-semantic density (ESD+). Analyses of the term 'feminist' in the Sociology of Sport for axiological semantic density (ASD) are also conducted. Meanings tend to be either neutral or positive but not pejorative in connotation. The overall contribution of the paper is to make visible and unpack the complexity of the term 'feminist' explicitly and systematically to scaffold student learning. The dense packaging might hinder newcomers to the Sociology of Sport field from accessing these specific meanings or constructing them in their own writing. Highlights: Legitimation Code Theory's Semantics to enact epistemological and axiological semantic density of 'feminist' in the Sociology of Sport. A 650, 000-word corpus offered 2044 occurrences of 'feminist' with a distribution of 229 different collocations. Making visible the complexity of 'feminist' might help newcomers to the Sociology of Sport access these specific meanings for their own writing.